Water quality characteristic of the National Hydraulic Research Institute of Malaysia (NAHRIM) lake undergoing remediation by the constructed wetlands: a baseline study - Aliyu, Aliyu Danjuma; Go, Rusea; Omar, Hishamuddin; Sharifuddin, Syazrin Syima; Mohamed Yusoff, Muhammad Azroie; Mohd Fazli, Bashirah (Universiti Putra Malaysia Press, 2019)
This study was conducted to determine the baseline water quality characteristics of a contaminated NAHRIM lake undergoing remediation by the constructed wetlands, based on the physico-chemical and biological parameters. The sampling was conducted for six months (May-October) in 2016 from 5 stations of the lake and analysed using APHA standard methods for water and wastewater analysis, while Malaysian water quality index (WQI) was used to calculate quality of the lake. The results showed that, the Conductivity, Dissolved Oxygen, NO3-N, NO2-N, PO4, Temperature, Turbidity, TDS, TSS, and Zn were under class I, while pH, B and COD were categorized under class II. NH3-N, BOD, Fe, Escherichia coli, Total coliform and Mn were categorized as class III. Moreover, Al was not given any classification under NWQS but their concentration did not exceed EPA guidelines. Furthermore, as compared to the water samples from the constructed wetlands that reported a class III WQI, the lake was observed to show an overall class II WQI. This is suggestive of the retaining and remedial role of the constructed wetlands being the first point of contact for the contaminants going to the lake. Thus the lake is suitable for recreational activities.